Evaluation of various substrates for spawn production and cultivation of Shiitake mushroom using Corn cobs. - Joshi, madhavi; Sagar, Anand (Mushroom Research, 2017)
Mushrooms have been considered as ingredient of gourmet cuisine throughout the world, especially for their unique flavor and have been valued by humankind as a culinary wonder. Owing to the medicinal properties and exotic flavor of Lentinus edodes, its cultivation has tremendously increased throughout the world as it can grow at a wide temperature range and can convert various agricultural wastes to food proteins. The present study was based to assess the spawn development of shiitake mushroom on different grains viz., wheat, barley, maize, soybean and pearl millet and its cultivation using whole corn cobs, a locally available agricultural residue which is otherwise not consumed by humans and is either burnt or left for natural degradation. Thus, shiitake mushroom provide a way for effective utilization of this residue by converting waste into food having therapeutic value.